2007
DOI: 10.1002/macp.200700053
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Branched Polyolefins by Metallocene Catalysis

Abstract: Metallocene/methylaluminoxane catalysts are able to design copolymers with tailored architectures. It is possible to copolymerize ethene with higher α‐olefins and cyclic olefins. The terpolymer of ethene/1‐hexene/norbornene shows a better flexibility than the ethene/norbornene copolymer by a similar high transparency. The influence of the comonomer concentration on activity, molecular weight, and glass transition temperature is given as well as the comparison to 1‐hexene/norbornene and propene/norbornene copol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…However, the number of catalysts that copolymerize norbornene with propene or higher 1-alkene is very limited, and their activity and/or the molecular weight of the produced polymers is not sufficient. [58][59][60][61][62][63] Ansa-dimethylsilylene(fluorenyl)(amido)dimethyltitanium-based catalysts were found to be active not only for 1-alkene polymerization but also for norbornene polymerization. We therefore applied these catalysts for copolymerization.…”
Section: Copolymerization Of Norbornene With 1-alkenementioning
confidence: 99%
“…However, the number of catalysts that copolymerize norbornene with propene or higher 1-alkene is very limited, and their activity and/or the molecular weight of the produced polymers is not sufficient. [58][59][60][61][62][63] Ansa-dimethylsilylene(fluorenyl)(amido)dimethyltitanium-based catalysts were found to be active not only for 1-alkene polymerization but also for norbornene polymerization. We therefore applied these catalysts for copolymerization.…”
Section: Copolymerization Of Norbornene With 1-alkenementioning
confidence: 99%
“…He et al [2] Extremely Color-Stable Blue Light-Emitting Polymers Based on Alternating 2,7-Fluorene-co-3,9-carbazole Copolymer Y. Cao et al [3] Tailored Branched Polyolefins by Metallocene Catalysis W. Kaminsky et al [4] Functional Star-Like Polystyrenes as Organic Supports of MeDIP(2,6-iPrPh) 2 FeCl 2 Catalyst Toward EthylenePolymerization H. Cramail et al [5] Synthesis of Functionalized NMP Initiators for Click Chemistry: A Versatile Method for the Preparation of…”
Section: Synthesis Of 3-arm Star Block Copolymers By Combination Of 'mentioning
confidence: 99%
“…The LG Chemical Group conducted the copolymerization of propylene, 1-hexene, and 1-octene using H 2 C(Me 2 C 5 H 2 ) 2 ZrCl 2 -methylaluminoxane. 17 Kaminsky et al 18 conducted the copolymerization of NB and 1-hexene using several metallocene catalysts. Hou et al 19 reported the copolymerization of 1-hexene and dicyclopentadiene with a cationic CpSc complex.…”
Section: Introductionmentioning
confidence: 99%